A Scheme for Jointly Trading off Costs and Risks of Solar Radiation Management and Mitigation Under Long-Tailed Climate Sensitivity Probability Density Distributions - Elnaz Roshan; Mohammad M. Khabbazan; Hermann Held (Environmental Modeling & Assessment, 2021)
Side effects of "solar-radiation management" (SRM) might be perceived as an important metric when society decides on implementing SRM as a climate policy option to alleviate anthropogenic global warming. We generalize cost-risk analysis that originally trades off expected welfare loss from climate policy costs and risks from transgressing climate targets to also include risks from applying SRM. In a first step of acknowledging SRM risks, we represent global precipitation mismatch as a prominent side effect of SRM under long-tailed probabilistic knowledge about climate sensitivity. We maximize a social welfare function for the following three scenarios, considering alternative relative weights of risks: temperature-risk-only, precipitation-risk-only, and equally-weighted both-risks. Our analysis shows that in the temperature-risk-only scenario, perfect compliance with the 2~°C-temperature target is attained for all numerically represented climate sensitivities, a unique feature of SRM, but the 2~°C-compatible precipitation corridor is violated. The precipitation-risk-only scenario exhibits an approximate mirror-image of this result. In addition, under the both-risks scenario, almost 90% and perfect compliance can be achieved for the temperature and precipitation targets, respectively. Moreover, in a mitigation-only analysis, the welfare loss from mitigation cost plus residual climate risks, compared to the no-climate-policy option, is approximately 4.3% (in terms of balanced growth equivalent), while being reduced more than 90% under a joint-mitigation-SRM analysis.
Keywords: 690; Climate targets; Cost-risk analysis; Decision making under uncertainty; Mitigation; Solar-radiation management